Measurement of the inclusive J/[psi] polarization at forward rapidity in pp collisions at √s=8 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Köhler, Markus Konrad; Klewin, Sebastian; Leardini, Lucia; Mercado Pérez, Jorge; et al. (The European physical journal. C, Particles and fields, 2018)
We report on the measurement of the inclusive J/ψψψ polarization parameters in pp collisions at a center of mass energy s√=8s=8\sqrt{s} = 8 TeV with the ALICE detector at the LHC. The analysis is based on a data sample corresponding to an integrated luminosity of 1.23 pb−1−1^{-1}. J/ψψψ resonances are reconstructed in their di-muon decay channel in the rapidity interval 2.5<y<4.02.5<y<4.02.5< y < 4.0 and over the transverse-momentum interval 2<pT<152<pT<152< p_T < 15 GeV/cGeV/cGeV/c. The three polarization parameters (λθλθλ _θ , λφλφλ _φ , λθφλθφλ _{θ φ }) are measured as a function of pTpTp_T both in the helicity and Collins-Soper reference frames. The measured J/ψψψ polarization parameters are found to be compatible with zero within uncertainties, contrary to expectations from all available predictions. The results are compared with the measurement in pp collisions at s√=7s=7\sqrt{s} = 7 TeV.
Im Titel wird psi als griechischer Buchstabe dargestellt
ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, M.C. Danisch, A. Deisting, V. Feuillard, P. Glässel, J. Kim, M.K. Köhler, S. Klewin, L. Leardini, J. Mercado Pérez, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, M.O. Schmidt, J. Stachel, D.F. Weiser, B. Windelband [und weitere]
Gesehen am 24.06.2019